Extended interpretation on Chinese Clinical Guidance for COVID-19 Diagnosis and Treatment(7the-dition,trial implementation):focused on hemodialysis - ZHOU Li; ZHONG Hui; FU Ping (Linchuang shenzangbing zazhi)
At the end of 2019, many cases of pneumonia caused by a 2019-nCoV were identified, and spread aggressively to entire China and other countries. In this article, we gave an extended interpretation on Chinese Clinical Guidance for COVID-19 Diagnosis and Treatment(7th edition, trial implementation) issued by National Health Committee of the People’s Republic of China, focusing on hemodialysis patients and related issues of COVID-19.